Modeling Differential Pressure of Diesel Particulate Filters in Marine Engines - Jaehwan Jang; Byungchae Min; Seongyool Ahn; Hyunjun Kim; Sangkyung Na; Jeongho Kang; Heehwan Roh; Gyungmin Choi (Energies, 2022)
The captured particulate matter (PM) in diesel particulate filters (DPF) must be periodically burned to maintain the performance and durability of the engine. The amount of PM in the filter must be monitored to determine a suitable regeneration period. In this study, the modeling parameters of the DPF were optimized using experimental data to determine a suitable regeneration period for the DPF for marine diesel engines. The differential pressure over the exhaust gas mass flow rate and temperature were measured using a fresh DPF. The modeling parameters of Darcy’s law were optimized using the experimental data. Finally, the model parameters were validated using differential pressure data obtained from a DPF containing PM. The proposed model, which is a function of the gas flow rate, temperature, and amount of collected PM, was developed to simulate the differential pressure of DPFs and shows potential for application in the development of regeneration logic for marine DPFs.